TINJAUAN UMUM ATAS TUJUH KESEPAKATAN PERDAGANGAN YANG TELAH DIIMPLEMENTASIKAN DI INDONESIA : SEBERAPA LIBERALKAH INDONESIA ? - Afriansyah Darwin (Badan Pendidikan dan Pelatihan Keuangan - Kementerian Keuangan Republik Indonesia, 2015)
Our analysis try to draw up Indonesia’s position in any economic integration agreement involved, bilaterally or regionally, which are ASEAN free trade area (ASEAN Trade in Goods Agreement), ASEAN-China Free Trade Area , ASEAN-India Free Trade Area, ASEAN-Korea Free Trade Area, Indonesia -Japan Economic Partnership Agreement, ASEAN-Australia-New Zealand Free Grade Area , dan Indonesia-Pakistan Preferential Trade Agreement, the rules of Trade in goods in each agreement, and moreover to analyze preferential tariff given based on minister of finance Decrees. The research conducted by literature study. Our analyze discover two conclusion, first, Indonesia has given tarif reduction and elimination according to the modality agreed in the integration agreement. We need to analyze further whether our partner has granted us the same commitment . Seconnd, related to the operational certification procedures (OCP), our analyze recommend the ruling of OCP through Minister of Finance Decree, to strengthen legal basis of certificate of Origin’s examination by the customs officer